2017
DOI: 10.1051/0004-6361/201730937
|View full text |Cite
|
Sign up to set email alerts
|

The GTC exoplanet transit spectroscopy survey

Abstract: Context. Transiting planets offer an excellent opportunity for characterizing the atmospheres of extrasolar planets under very different conditions from those found in our solar system. Aims. We are currently carrying out a ground-based survey to obtain the transmission spectra of several extrasolar planets using the 10 m Gran Telescopio Canarias. In this paper we investigate the extrasolar planet WASP-48b, a hot Jupiter orbiting around an F-type star with a period of 2.14 days. Methods. We obtained long-slit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Ground-based observations have also proved to be successful in correcting for the telluric effects by applying the differential spectrophotometry method. These observations are mostly carried out with multi-object spectrographs mounted on large telescopes, for example, FORS2 on the Very Large Telescope (VLT; Lendl et al 2016;Nikolov et al 2016;Sedaghati et al 2016), OSIRIS on the Gran Telescopio Canarias (Chen et al 2017a;Murgas et al 2017), GMOS on the Gemini telescope (Gibson et al 2013;Todorov et al 2019), IMACS on the Magellan telescope (Rackham et al 2017;Espinoza et al 2019), and MODS on the Large Binocular Telescope (LBT; Mallonn & Strassmeier 2016). These ground-based observations provide transmission spectra in the optical wavelength range that cover features such as Na/K (Sing et al 2012;Lendl et al 2017;Chen et al 2018;Nikolov et al 2018;Pearson et al 2019), TiO/VO (Sedaghati et al 2017), and the Rayleigh-scattering slopes (Nikolov et al 2015;Parviainen et al 2016;Kirk et al 2017;Chen et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Ground-based observations have also proved to be successful in correcting for the telluric effects by applying the differential spectrophotometry method. These observations are mostly carried out with multi-object spectrographs mounted on large telescopes, for example, FORS2 on the Very Large Telescope (VLT; Lendl et al 2016;Nikolov et al 2016;Sedaghati et al 2016), OSIRIS on the Gran Telescopio Canarias (Chen et al 2017a;Murgas et al 2017), GMOS on the Gemini telescope (Gibson et al 2013;Todorov et al 2019), IMACS on the Magellan telescope (Rackham et al 2017;Espinoza et al 2019), and MODS on the Large Binocular Telescope (LBT; Mallonn & Strassmeier 2016). These ground-based observations provide transmission spectra in the optical wavelength range that cover features such as Na/K (Sing et al 2012;Lendl et al 2017;Chen et al 2018;Nikolov et al 2018;Pearson et al 2019), TiO/VO (Sedaghati et al 2017), and the Rayleigh-scattering slopes (Nikolov et al 2015;Parviainen et al 2016;Kirk et al 2017;Chen et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…If sodium, and in some cases, potassium measurements based on low-resolution spectra were reported (e.g., for some of the most recent ones, Sedaghati et al 2016;Chen et al 2017;Pallé et al 2017;Murgas et al 2017;Lendl et al 2017;Chen et al 2018;Pearson et al 2019), only a few studies detected sodium using highresolution transmission spectroscopy: Wyttenbach et al (2017) registered strong absorption signal in WASP-49b. Using HARPS-N mounted on the TNG, Casasayas- Barris et al (2017) andCasasayas-Barris et al (2018) concluded to the presence of sodium in the atmospheres of WASP-69b and MASCARA-2b.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Tsiaras et al (2017) did a reanalysis of the Hubble observations for 30 exoplanets in order to provide a uniformly reduced and analyzed sample of planets. At optical wavelengths, numerous ground-based observatories are working on surveys; including the ACCESS group, also at the Magellan telescopes at Las Campanas, with results for GJ 1214 b (Rackham et al 2017); and the Gran Telescopio Canarias exoplanet transit spectroscopy survey, currently with results for numerous planets (see Sing et al 2012;Murgas et al 2014;Parviainen et al 2016;Pallé et al 2016;Nortmann et al 2016;Chen et al 2017a,b;Murgas et al 2017;Parviainen et al 2017). Because telescope time is limited, it is important to make use of all resources available to us to study the atmospheres of new planets, as well as ensure reproducibility of results across telescopes, instruments, and reduction methods.…”
Section: Introductionmentioning
confidence: 99%